Innovation of Integrated Personnel Information Management Application System (E-Pinisi) in Bappelitbangda, South Sulawesi Province - Aslinda, Aslinda; Nurhalifah, Nurhalifah; Nur, Andi Cudai (Jurnal Aktor, 2024)
This study aims to determine the Innovation of the Integrated Personnel Information Management Application System (E-Pinisi) in BAPPELITBANGDA, South Sulawesi Province. This research includes descriptive qualitative research with data collection techniques through observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation and conclusions.The results showed that the Innovation of the Integrated Personnel Information Management Application System (E-Pinisi) in BAPPELITBANGDA South Sulawesi Province has provided innovation in realizing Good Governance, this is evidenced by Roger's (2003) innovation characteristic indicators, namely: 1) Relative Advantage, 2) Compatibility, 3) Complexity, 4) Triability, 5) Observability. that in general, the innovation of the integrated personnel information management application system (E-Pinisi) in BAPPELITBANGDA South Sulawesi Province is good, but it needs to be optimized on the Complexity indicator.